Clump breakage algorithm for DEM simulation of crushable aggregates - Brzeziński, Karol; Gladky, Anton (Tribology international, 2022)
The paper presents a new clump breakage algorithm for DEM simulation of crushable aggregates. We emphasize some issues related to the modeling of rigid clump breakage and abrasion (e.g., no interactions between clump members, the theoretical mass of clump members higher than the mass of the clump). The algorithm presented in this paper tackles those issues. Correction to the Love-Weber stress tensor is proposed, which allows estimating the stress state of clump members separately. Also, we presented the splitting algorithm that conserves the mass in the system without introducing excessive potential energy coming from particles overlapping. The adapted strength criterion allows for capturing the size effects. The algorithm was implemented in the Yade software and is freely available. •The algorithm presented allows for modeling splitting and abrasion of rigid clumps of spheres.•The mass in the system is conserved after particle breakage.•Mohr-Coulomb-Weibull criterion is implemented to account for scale effects.•Example simulations are presented, including breakage of particles during oedometric test and wear.